EDUCATIONAL VIDEO RELATED TO COVID-19 AND VACCINATION FOR THE COMMUNITY - Zen Hafy; Venny Larasati; Soilia Fertilita; Dwi Handayani (Conferences of Medical Sciences Dies Natalis, 2021)
One of the efforts being promoted by WHO to prevent Covid-19 is vaccination. Vaccination aims to prevent the symptoms of a disease caused by pathogenic infection. In some cases, vaccination does not prevent infection but can limit the consequences of the infection. Some of the obstacles encountered in the community include the lack of public knowledge about vaccination, a lot of negative news that develops in the community about vaccination, and the availability of vaccines for the community is still limited. Efforts to educate the public have been carried out to increase public awareness about the benefits of vaccination, either through direct counseling by agencies engaged in the health sector or through social media. Such efforts need to be carried out massively and continuously so that education can reach all levels of society. This community service activity program is carried out by producing educational videos that will target all population levels to provide information about Covid-19 management and clarifications on some most common incorrect information or even myths about Covid-19 vaccination and give the public in Indonesia a chance to learn the facts about the Covid-19 vaccine.